Vascular and Cardiorespiratory Factors are Associated with Functional Capacity in Patient with Type 2 Diabetes Mellitus - Ni Made Elva Mayasari; Raden Ayu Tanzila; Namira Amanda; Woro Nurul Sandra Anindhita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TIntroduction Diabetes mellitus is a degenerative disease that has globally increasedprevalence annually 1 . Impaired functional capacity due to poor blood sugar controland presence of cardiovascular autonomic dysfunction. Six minute walk test is amethod that is widely used in the assessment of functional capacity in patients withType 2 Diabetes Mellitus.ObjectiveTo evaluate factors that are associated withfunctional capacity in Type 2 Diabetes Mellitus.Methods This is an analyticobservational study with a cross sectional design. Fourty patients who had beendiagnosed with diabetes mellitus was assessed by six minute walk test. Chi squareand logistic regression analysis was perform by using SPSS 25. Results Six minutewalk test correlated significantly with Ancle Brachial Index scores (p = 0.016) andBody Mass Index (p = 0.03) Conclusion Ancle Brachial Index Score and Body MassIndex are factors associated with functional capacity in Type 2 Diabetes Mellitus